Liver metastatic colonization by invasive cancer cells: a review of potential biomarkers with mitochondrial involvement - Daniel L. Pouliquen (Exploration of Digestive Diseases, 2024)
The liver, characterized by a unique metabolic and immunosuppressive environment, is also the organ to which invasive malignant cells of many different cancer types most frequently metastasize. The reasons for this organ-specific metastatic process have been investigated for decades. This review first provides an overview of recent breakthroughs in this field, introducing intercellular communication between circulating tumor cells and the heterogeneous cell populations of the liver, and modifications to the extracellular matrix (ECM). Subsequently, to improve the understanding of the molecular mechanisms involved in the metastasis of colorectal cancer to the liver, the second leading cause of cancer-related mortality, the recent literature on this question was analyzed. Among the various parameters involved, the mechanisms behind the activation of hepatic stellate cells, proteins inducing ECM remodeling, specific genomic features of liver metastases, metabolic rewiring, and characteristics of stromal-enriched microenvironments were discussed. To provide more insights into the molecular determinants of liver metastatic colonization, important findings reported on a set of mitochondrial proteins were addressed, the relative abundance of which changed in the liver during the progression stage of an aggressive experimental model of peritoneal malignant mesothelioma in immunocompetent rats. Based on previous studies cross-comparing the liver proteomes from curcumin-treated tumor-bearing rats/untreated tumor-bearing rats/normal rats, data from the literature were reviewed for 25 mitochondrial proteins of interest. Their role in lipid metabolism, heme biosynthesis, the electron transport chain, small molecule transport, mitochondrial dynamics, the tricarboxylic acid cycle, and protection against oxidative stress were analyzed in the context of both cancer and non-malignant liver diseases.